Serve performance analysis of men ´s professional tennis - Gallego, R. M.; Guzman Lujan, J. F.; Mas, J. R.-L.; Santamaria, C. G. (Journal of Human Sport & Exercise, 2018)
Introduction: The serve is considered one of the most important shots for the performance of professional tennis players. The influence of the serve causes most points to have a duration of less than 5 strokes, and it is also the server who wins most of these points. The objective of this study was to verify which variables related to the serve are critical in the success of it. Material and methods: A total of 1119 serves in 8 matches at the 2011 ATP tournament 500 Valencia were recorded and analysed using SAGIT, a computer vision tracking system. Points were compared between points (a) won by the server with less than 5 shots with (b) points with more than 5 shots or lost by server.Results and discussion: There were differences between (a) and (b) in the type of serves (first or second), time between shots (serve and return) and returner speed between serve and return. Points won by the server with less than five shots were played with a first serve, the time between serve and return of serve was lower than the rest of the points, and the average and maximum speed of the returner was greater in these points. There were no differences in terms of the direction of the serve and the distance covered by the returner between serve and return of the serve.